Velhas e velhos conquistam espaços nas universidades de São Paulo: política, sociabilidade e educação - Ramos, Vania (2008)
This thesis focuses primarily on the following items: different visions on aging, an analysis of the historical path of the so called open universities of the Third Age (U3A) in order to bring them into the context of the universities located in the city of São Paulo; a qualitative research was developed, based on an analytical study on two distinctive projects for universities for the elderly in the city of São Paulo (the Open University of the third age of USP Universidade de São Paulo and the University for the elderly of PUC / SP Pontifícia Universidade Católica de São Paulo), applying questionnaires and personal interviews with some students from these universities. The next chapter develops an analysis based on these students answers and statements. Finally, the discovery of a new form of ageing, a lifestyle for the elderly that we envision as innovative